Disability advocacy messaging and conceptual links to underlying disability identity development among college students with learning disabilities and attention disorders. Issue 1 (January 2020) - Kreider, Consuelo M.; Luna, Claudia; Lan, Mei-Fang; Wu, Chang-Yu
Abstract: Background: Learning disabilities and attention disorders (LD/AD) are highly prevalent neurodevelopmental conditions that influence developmental trajectories and whose impacts exist throughout the life course. Self-advocacy skills are critical for college students with LD/AD, which are underpinned by understanding of self and one's disability. Objective: This study examined disability advocacy messaging included in projects created by college students with LD/AD, compared patterns in disability messaging to existing disability identity models, and explored changes in disability messaging during receipt of holistic campus-based LD/AD supports. Methods: Participants were 52 undergraduates with LD/AD enrolled in a larger study. This one-group analysis involved qualitative exploration of the projects' topical content, use of grounded theory procedures for conceptualizing the data, and quantitative analysis to explore changes over time in disability advocacy messaging. Results: Participants messaged a broad range of disability-related topics. A five-level theoretical model of disability messaging was created from the textual data. The model evinces parallels to existing disability identity development models. A significant ( p <  .01) positive shift in disability messaging was observed in a comparison of messages from participants' first and last projects submitted over the four-semester period of study involvement. Conclusion: Study findings support conceptual linkages among disability messaging and disability identity development. The resultant continuum model suggests a potential extension of existing disability identity development paradigms. Shifts in disability messaging provide preliminary evidence for potential personal and institutional benefits of engaging college students with LD/AD in disability-focused project creation.